DISPERSION PREDICTION OF CO, NO2, SO2, PM10, AND PM2.5 POLLUTANTS IN THE CITY AND REGENCY OF TANGERANG USING AERMOD SOFTWARE - Shinta Widyanti, Angela
Air pollution is one of the most important environmental health problems because it can cause death, illness, and have a wide impact on many sectors. One of the most important aspects in analyze air quality problems is the analysis of pollutant dispersion models which establish a relationship between emissions released to the concentration distribution and the area affected so that they have the potential to provide information on possible future air quality. This study conducted pollutant dispersion modelling for Tangerang City and Tangerang Regency. These two regions were selected as study areas because of their rapid development and have become the supporting cities for the Jakarta area. This modelling is derived from the emission load from the 2017 emission inventory for Tangerang City and Regency in the transportation sector, the industrial sector, the power generation sector, the residential sector, the agricultural sector, and the livestock sector. The result of concentration modelling using AERMOD CO emission for an average of one hour is 7793 µg/Nm3 and an average of 8 hours is 5926 µg/Nm3, NO2 emission for an average of 1 hour is 370.6 µg/Nm3, average 24-hours average is 181 µg/Nm3, and the one-year average is 122 µg/Nm3, SO2 emission for 1 hour average is 102.6 µg/Nm3, 24-hours average is 53.1 µg/Nm3, and the one-year average is 32.7 µg/Nm3, the PM10 emission for a 24-hours average is 28 µg/Nm3and the one-year average is 12.25 µg/Nm3, as well as emissions The PM2.5 for a 24-hours average is 18.85 µg/Nm3and a one-year average is 11.26 µg/Nm3. The modelling results show that the 8- hours average of CO and NO2 parameters exceed the ambient air quality standards issued by Government Regulation No. 22/2021. The most affected areas with high concentrations of pollutants are in the Batuceper and Cipondoh districts, Tangerang City.